Penggunaan Media Berbasis AI untuk Menumbuhkan Peduli Lingkungan Sejak Dini Terhadap Sampah: The Use of AI-Based Media to Foster Environmental Care From an Early Age Against Waste - Anjarsari, Irna; Erni Suharini; Arif Widiyatmoko (Universitas Ngudi Waluyo, 2025)
Environmental awareness about waste plays a very important role in the sustainability of the next life. How environmental awareness from an early age can understand waste management can be done with fun learning and of course according to the current generation of artificial intelligence. The purpose of this study is to provide an overview of the use of artificial intelligence (AI) in the Canva AI application